2018
DOI: 10.2987/18-6754.1
|View full text |Cite
|
Sign up to set email alerts
|

Residual Pesticide On Hesco® Blast Protection Wall In Temperate Florida Habitat Effective Against Mosquitoes, Stable Flies, and Sand Flies

Abstract: United States military troops in the field are exposed to the environment and are thus at high risk for transmission of arboviruses, and degradation of mission from continual harassment from insects. Passive vector control, such as application of residual insecticides to US military materials common in the field such as tents and camouflage netting, has been shown to be effective and can contribute to a successful integrated vector management (IVM) plan in the field to reduce this risk. However, other common U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…For example, Britch et al (2011) reported reduction of mosquito numbers inside open-top enclosures of US military camouflage netting in a hot-arid environment in southern California when the surface of the fabric wall was treated with a residual insecticide. The significance of this finding is that a passive layer of control may be automatically situated in the field by pretreatment of materials such as camouflage netting, tent exteriors (Frances 2007), or blast wall geotextile (Britch et al 2018) that are already organic to deploying US military units.…”
mentioning
confidence: 99%
“…For example, Britch et al (2011) reported reduction of mosquito numbers inside open-top enclosures of US military camouflage netting in a hot-arid environment in southern California when the surface of the fabric wall was treated with a residual insecticide. The significance of this finding is that a passive layer of control may be automatically situated in the field by pretreatment of materials such as camouflage netting, tent exteriors (Frances 2007), or blast wall geotextile (Britch et al 2018) that are already organic to deploying US military units.…”
mentioning
confidence: 99%
“…Residual pesticide treatment of US military materials is important in military integrated vector management (IVM) because these materials exist nearly everywhere US military personnel are positioned in the field. Pretreatment of US military field materials, such as tents (Frances 2007), camouflage netting (Britch et al 2011), or the geotextile in blast protection walls (Britch et al 2018), with a residual pesticide could automatically establish the 1st layers of an effective IVM system when these materials, already organic to units deploying to austere environments, are formed into perimeters around outposts or bivouacs. However, host-seeking mosquitoes may still enter perimeters treated with standard residuals, such as k-cyhalothrin, without contacting treated surfaces or may contact treated surfaces but retain mobility and host-seeking behavior long enough to contact humans (Britch, personal observations;Viana et al 2016), and in the long run this technique could induce the evolution of resistance because the treatment is lethal to target insects (Hoy 1998).…”
mentioning
confidence: 99%
“…On August 5, 2013, we set up 5 experimental enclosures constructed of brown geotextile HESCO MIL barriers (Szabó et al 2011) following the methods described in Britch et al (2018) in a hot-arid desert site in the Coachella Valley, CA (Britch et al 2009). We oriented the 5 enclosures in an approximate north-south line among sparse vegetation, each separated from the next by approximately 25 m. We treated the northernmost 2 HESCO enclosures and the southernmost 2 enclosures with k-cyhalothrin as described in Britch et al (2018), leaving the middle enclosure as an untreated control unit.…”
mentioning
confidence: 99%
“…We obtained H. convergens specimens through a commercial supplier (Arbico Organics, Oro Valley, AZ) in batches of 1200 every week for 3 wk in July 2014. Colony histories of the remaining colony organisms are described in Britch et al (2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation